Managing Supplier Satisfaction: Social Capital and Resource Dependence Frameworks. Issue 2 (May 2015) - Schiele, Holger; Ellis, Scott C.; Eßig, Michael; Henke, John W.; Kull, Thomas J.
Recently, supplier satisfaction has gained more attention both in practice and in academic research. However, the knowledge accumulation process is still in an embryonic and explorative phase. Likewise, supplier satisfaction measuring in practice may still benefit from an impetus from academia to be more widely used. This paper aims at considerably expanding understanding of supplier satisfaction by proposing to apply a social capital and a resource dependence theory perspective. We expect an abundance of social capital in a relationship to relate positively to supplier satisfaction, whilst power disequilibrium and dependence from the buyer are expected to negatively relate to supplier satisfaction. It is worth highlighting that, according to research rooted in Hofstede's cultural dimensions model, the perception and acceptance of power differences resulting from a situation of dependency is highly culture specific. We therefore further hypothesise that supplier satisfaction will be moderated by cultural differences and ask researchers to take the cultural dimension into account.